A study of practicing degree of schools principals in dealing with students positive behaviors - Bassam Mahmoud Bany Yassien; Najwa Abedalhameed Draawsheh (Intelektual Pustaka Media Utama, 2020)
The importance of the study is to find out the relationship of how school principals dealing with positive behavior of students in Irbid first educational Directorate, in order to shed light 0n these practice to promote students positive behavior. The study aimed to identify the practice degree of secondary school principals at Irbid First Educational Directorate toward their administrative and technical tasks and its relationship with the positive behaviors of students, from teachers' standpoint. Study sample consist of 310 male and female teachers who were selected through the simple random method from the 1022 study population members, and to achieve the study objectives, researcher developed a questionnaire as the study tool and was checked to ensure its sincerity and reliability. The study results showed that the practice degree of secondary school principals at Irbid First Educational Directorate toward their administrative and technical tasks, from the teachers' standpoint came to a medium degree, while there weren’t any statistically significant differences according to the qualification and experience variables. The results showed that practice degree of secondary school students toward the positive behavior, from teachers' standpoint came to a medium degree, and also showed a statistically significance correlation at level (α = 0.05) between student's behavior toward school and colleagues, and the positive attitude of students as a whole and the practice degree of secondary school principals toward their administrative and technical tasks.